Use of a Topical Film-Forming Medical Device Containing Repairsomes® in a Patient with Xeroderma Pigmentosum to Avoid Progression to Skin Cancerization - González-Morán A; Piquero-Casals J (Clinical, Cosmetic and Investigational Dermatology, 2020)
Alfonso González-Morán,1 Jaime Piquero-Casals2 1Sección de Dermatología del Hospital de Nuestra Señora de Sonsoles, Ávila, Spain; 2Dermik, Multidisciplinary Dermatological Clinic, Barcelona, SpainCorrespondence: Jaime Piquero-CasalsDermik, Multidisciplinary Dermatological Clinic, Barcelona, SpainTel +34 935464710Email j.piquero@dermik.esAbstract: This paper reports a case of xeroderma pigmentosum in a 78-year-old woman with a 17-year history of multiple basal cell carcinomas, keratoacanthoma, and lentigo maligna melanoma, in different photoexposed facial regions. To prevent aggravation of these medical conditions, for five years, the patient had been applying a film-forming topical medical device (MD) containing the DNA-repair enzyme photolyase in liposomes and high-protection UV ﬁlters (Repairsomes) twice a day. During this time, the patient had no clinical or dermatoscopic evidence of new skin cancer lesions. However, at her last visit, the patient had a new basal cell carcinoma on the face, in the right supramaxillary area. After questioning, the patient recognized that she had not been applying the product on a regular basis during the last year. This may have been a coincidence; however, there is clinical evidence of the preventive effect of this MD in reducing the cancerization field and consequently the development of skin cancer. This product contains a light-activated flavoenzyme called photolyase which creates the condition to revert cyclobutane pyrimidine dimer. In the discussion of this case, we review recent publications and stress some important aspects on the role of photoprotection and photorepair as a strategy to more effectively reduce the risk of UV-induced premalignant and malignant skin lesions compared to traditional photoprotection strategies.Keywords: xeroderma pigmentosum, lentigo maligna melanoma, skin cancer, cancerization field, sunscreen, photolyase, non-melanoma skin cancer, melanoma